ANALYSING THE VALUE AND NON-VALUE ACTIVITIES USING ACTIVITY-BASED MANAGEMENT CONCEPT AT PT. CELEBES MINA PRATAMA BITUNG - Kalaena, Riskabella . (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: In modern times, many companies of business industries in Bitung City especially in the fisheries sector are facing the tighter competition. That make every company want to give the best performance for customer with minimize the time and cost. The purpose of this study to analyze if there are non-value added activities at process production of wood fish at PT. Celebes Mina Pratama Bitung. This research using qualitative method that will identify the value and non-value activities at company and type of research is descriptive research. Population in this research is all employees who work at PT. Celebes Mina Pratama. There are 2 methods to collecting the data which are: primary data and secondary data such as; interview, observation and documentation. The result of this research shows if activity based management (ABM) concept is very useful to find out the non-value added activities at the company and the production process effectiveness in the company is good enough because it almost reaches 100% which are 95,45% for Katsuo Arahonbushi (KH) and 95,37% for Katsuo Arakamebushi (KK) that means the company need evaluation of each activity and process that exists. Researcher recommend for company to using ABM concept in their production process. Keyword : activity-based management, manufacturing cycle effectiveness, value added activity, non-value added activity